Scientific Writing Training Through Hybrid Experiential Learning Strategies for Pondok Pesantren Teachers - Sobri, Ahmad Yusuf; Muslihati; Taufiq, Ahmad; Saputra, Nur Mega Aris; 'Ilmi, Achmad Miftachul (Universitas Nahdlatul Ulama Surabaya, 2024)
The implementation of this activity aims to improve the skills of writing scientific papers for teachers within the scope of the Zainul Hasan Genggong Islamic Boarding School Probolinggo. The hybrid experiential learning strategy used in the implementation of scientific writing training is a combination of reflective, continuous and project-based learning. Scientific writing training activities for Islamic boarding school teachers are carried out boldly and attractively which are useful for maximizing the expected skill achievement. The above training activities have several stages as follows (1) finding out, ideas and basic scientific studies; (2) preparation of theoretical studies; (3) research design methods; (4) writing scientific articles; and (5) journal selection and article submission. At each stage of the assignment participants' activities and reviews to determine the understanding and skills acquired. The results of the implementation of scientific work training for Islamic boarding school teachers through a hybrid experiential strategy show that Islamic boarding school teachers can identify ideas or problems within the scope of their study and write them into scientific works.